Respuesta :

The factors of given equation are -3/4 and -2.

Rewriting the equation -

4x² + 11x + 6 = 0

The factors for the given expression will be calculated based on two factors -

1. The sum of factors should be equal to sum of numeral value of b (11 in this case)

2. The product of factors should be equal to product of numeral values of a and c (24 in this case)

As per the above rules, the appropriate factors should be 8 and 3.

Rewriting the given equation with possible factors -

4x² + 8x + 3x + 6 = 0

Taking common values

4x(x + 2) +3(x + 2) = 0

(x + 2) (4x + 3) = 0

x = -3/4, -2

Thus, the factors of given expression are -3/4 and -2.

To check the correctness of factors, we will keep each value of x in equation.

When x = -3/4

4x² + 11x + 6 = 0

4(-3/4) + 11(-3/4) + 6 = 0

9/4 -33/4 + 6 = 0

9/4 = 2.25 and 33/4 = 8.25

2.25 - 8.25 + 6 = 0

-6 + 6 = 0

0 = 0

When x = -2

4x² + 11x + 6 = 0

4(-2)² + 11(-2) + 6 = 0

16 - 22 + 6 = 0

22 - 22 = 0

0 = 0

Since both values of x give 0 on both sides of equation, the factors of equation are correct.

Learn more about factorizing -

https://brainly.com/question/24734894

#SPJ4